An investigation into the relationship between information and environmental behaviour : a case study of Cape Town's Smart Living Campaign - Buckton, Karl (Department of Environmental and Geographical Science, 2015)
Environmental campaigns have generally relied upon using information alone as a way to get messages across to the public. This approach is based on the assumption of a linear relationship between information and behaviour: it is believed that educating people will lead them to be more environmentally responsible. An example of this is the information deficit model. The information-deficit model (Blake, 1999), suggests that experts inform individuals about the environment in order to achieve behaviour change. Contrary to this model, dissenters claim that the information-deficit model is not participatory or deliberative and that human behaviours are determined by factors such as individual lifestyle. This dissertation tests the assumption behind the idea that added information leads to improved environmental behaviour. The research used a case study of an urban South African environmental education program: the Smart Living Campaign in the City of Cape Town. The study is split into two sections, the first which focuses on the workplace of the companies. The second which is aimed at the households of the employees of the companies. The study focused on two variables, the impact of waste management in terms of recycling, and energy usage in terms of electricity consumption on their behaviour.